2023
DOI: 10.1101/2023.03.07.529561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheVibrio fischeritype VI secretion system incurs a fitness cost under host-like conditions

Abstract: The type VI secretion system (T6SS) is an interbacterial weapon composed of thousands of protein subunits and predicted to require significant cellular energy to deploy, yet a fitness cost from T6SS use is rarely observed. Here, we identify host-like conditions where the T6SS incurs a fitness cost using the beneficial symbiont, Vibrio fischeri, which uses its T6SS to eliminate competitors in the natural squid host. We hypothesized that a fitness cost for the T6SS could be dependent on the cellular energetic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Alternatively, T6SS expression may incur environmentally dependent costs independent of metabolism. For example, recent work has found that the T6SS is strongly selected against within animal models (Robitaille et al., 2023; Septer et al., 2023), though further work will be required to determine the precise mechanistic cause. Taken together with our findings, these results suggest that while the expression of the T6SS is not inherently metabolically costly, it may incur context‐dependent ecological costs (e.g., through triggering host immune response (Gupta et al., 2021; Ma & Mekalanos, 2010), or via emergent consequences of changed ecological dynamics (Robitaille et al., 2023)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, T6SS expression may incur environmentally dependent costs independent of metabolism. For example, recent work has found that the T6SS is strongly selected against within animal models (Robitaille et al., 2023; Septer et al., 2023), though further work will be required to determine the precise mechanistic cause. Taken together with our findings, these results suggest that while the expression of the T6SS is not inherently metabolically costly, it may incur context‐dependent ecological costs (e.g., through triggering host immune response (Gupta et al., 2021; Ma & Mekalanos, 2010), or via emergent consequences of changed ecological dynamics (Robitaille et al., 2023)).…”
Section: Discussionmentioning
confidence: 99%
“…Given its hypothesized multi‐megadalton size, complexity, and conservative developmental regulation, prior work has inferred that the T6SS must be metabolically costly to maintain and utilize (Alteri & Mobley, 2016; Ho et al., 2014; Smith et al., 2020; Unni et al., 2022). However, recent experiments have not detected a measurable fitness effect of T6SS expression over 24 h of growth in rich media (Robitaille et al., 2023; Septer et al., 2023). Single‐day growth curves have a relatively low sensitivity, however, as they can only measure competitive outcomes over a small number of generations, and are thus ineffective for measuring traits with a small impact on fitness (Yokota & Sterner, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The incentive for bacteria to evolve such a genomic switch, could be the possibility to deactivate the expression of dispensable and energy-costly molecular machineries. Recent studies on Vibrio, Pseudomonas, and Bacteroides strains suggest that T6SS activity does in fact come with a fitness cost and it may be beneficial to regulate its activity (Drebes Dörr et al, 2022;Septer et al, 2023;Perault et al, 2020;Robitaille et al, 2023).…”
Section: Insertion Sequence Elements: Regulation Of Ixotrophy Dependi...mentioning
confidence: 99%
“…It is in this last clade where all members show vertical transmission (Figure 3). T6SS are multiprotein complexes and thus likely to be costly to produce and use ( [22] but see [23]). Their loss in endosymbionts supports a model where reduced competition within the endosymbiotic niche reducing the benefits of maintaining T6SS.…”
Section: Figure 2 Genomic Characteristics Of the Arsenophonus/riesia ...mentioning
confidence: 99%